1996
DOI: 10.1111/j.1365-3121.1996.tb00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐orogenic Svecofennian deformation in SW Finland constrained by pegmatite emplacement ages

Abstract: Late stages of the Svecofennian orogeny in SW Finland were related to a tranpressional stress field and dextral movements along crustal scale shear zones under decreasing temperature and pressure conditions. In the Kemiö area, a minimum estimate for the time span of movements along one of these shear zones is obtained from the ages of 1840 to 1830 Myr‐old microcline granite sheets, related to early ductile deformation, and by dating structurally late rare‐mineral granite pegmatites, related to brittle deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…The granites were subsequently refolded in open folds with E-W trending fold axes. Lindroos et al (1996) dated a pegmatite in the Kemiö area and concluded that transpressional deformation lasted until 1803 Ma. As the overall structural pattern in the LSGM zone differs from that in the Loimaa area, where the E-W to NE-SW trending structures were developing already 1870 Ma ago, it is difficult to apply this model to the Loimaa area.…”
Section: Discussionmentioning
confidence: 99%
“…The granites were subsequently refolded in open folds with E-W trending fold axes. Lindroos et al (1996) dated a pegmatite in the Kemiö area and concluded that transpressional deformation lasted until 1803 Ma. As the overall structural pattern in the LSGM zone differs from that in the Loimaa area, where the E-W to NE-SW trending structures were developing already 1870 Ma ago, it is difficult to apply this model to the Loimaa area.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphase deformation, metamorphism, migmatisation and magmatic activity ranges in age from about 1890 to 1800 Ma (Ehlers et al, 1993;Lindroos et al, 1996). Magmatic activity included dyke-like intrusion of minor mafic magmas and abundant pegmatites into high metamorphic grade (up to anatexis) metasediments and granitoid complexes.…”
Section: Bead Strings In the South Finland Migmatite-granite Beltmentioning
confidence: 99%
“…It contains about 1 wt% SnO 2 (i.e., 0.04 p.f.u.) and was dated at 1,802.9 ± 1.3 Ma (2r; Lindroos et al 1996). Material from the same, highly evolved pegmatite was taken by Pesonen (1999) and Pesonen et al (1999) for a palaeomagnetic study.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…There is a tendency toward Mn-rich and Ta-rich compositions with pegmatite evolution, although there may be differences depending on tectonic setting and concomitantly melt source of the pegmatites (e.g., Cerny 1982aCerny , b, 1991. For this study, we selected columbite-tantalite minerals from the Svecofennian (Broddbo, Kolsva, Kimito) and Sveconorwegian (Tveit, Torsgruvan, Tangen, Vintergruvan, Karlshus) provinces of Finland, Sweden, and Norway, as well as from a Kibaran pegmatite (Ruhmebe) of Burundy (see Table 1), that had been previously dated by the U-Pb method (Romer and Lehmann 1995;Lindroos et al 1996;Romer and Smeds 1997). With the exception of samples Kimito and Broddbo, the investigated columbite-tantalite samples have low contents of Ti, W, and Sn, which may substitute for Nb and Ta, and low contents of Mg, Ca, and Sc, which may substitute for Mn and Fe (cf.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation